EATING PERFORMANCE IN RELATION TO FOOD AND FLUID INTAKE IN NURSING HOME RESIDENTS WITH DEMENTIA. (11th November 2018) - Liu, W; Williams, K; Batchelor-Murphy, M; Perkhounkova, E; Hein, M
Abstract: Background: Nursing home (NH) residents with dementia commonly experience low intake leading to negative nutritional and functional outcomes. While multilevel factors at resident, caregiver and environmental levels are examined, evidence is lacking on the factors associated with the eating performance process. Objectives: To examine the association between food and fluid intake and eating performance among NH residents with dementia. Methods: A secondary analysis of 111 pre-intervention mealtime videos from a dementia trial was conducted. The videos involved 25 residents and 29 staff (42 dyads) in 9 NHs. Eating performance characteristics including type (eating solids, drinking liquids), technique (self-feeding, staff-facilitated feeding), and duration of each eating performance cycle were coded using a coding template with good feasibility and inter-rater reliability. The Generalized Linear Mixed Model was used. Results: Totally 1122 eating performance cycles were coded, and the majority (85.74%) resulted in intake. There were significant interactions for duration by technique, and duration by type. As the duration increased, staff-facilitated cycles resulted in greater intake than resident-completed cycles (OR = 17.173 vs. 2.530), and drinking resulted in greater intake than eating (OR =13.245 vs. 3.280). Further, resident-completed drinking and eating activities resulted in 3 and 8 times greater likelihood of intake, respectively, compared to staff-facilitated activities. Conclusions: The findings demonstrate the importance of supporting self-feeding, providing drinks when residents resist or struggle, and trying longer attempts to engage residents to improve intake. The findings inform the development and implementation innovative mealtime assistance and staff trainings to promote eating performance and intake.